Working From Home Phenomenon As an Effort to Prevent COVID-19 Attacks and Its Impacts on Work Productivity - Duta Mustajab; Azies Bauw; Abdul Rasyid; Andri Irawan; Muhammad Aldrin Akbar; Muhammad Amin Hamid (Universitas Airlangga, 2020)
COVID-19 attacks have changed the methods and cultures of work in many organizations, the working from home (WFH) phenomenon as an effort to prevent the spread of COVID-19 in many countries in the world has impacts on employee productivity. This study aims to explore the impacts of working from home on employee productivity with a qualitative approach. The findings explain that working from home has provided advantages and disadvantages both for employee and organization as well as being responsible for the decline in employee productivity. Furthermore, we also find the fact that working from home cannot be generally accepted since many areas of work cannot be carried out from home, although for many employees, working from home has provided a work-life balance. Yet, this is sometimes interrupted by multiple jobs (multitasking) that must be done at home.